2019
DOI: 10.1038/s42004-019-0211-7
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary-assisted chemical ubiquitylation of NEMO and linear extension by HOIP

Abstract: The ubiquitylation of NF-κB essential modulator (NEMO) is part of the intracellular immune signalling pathway. Monoubiquitylated NEMO is required for exploring the mechanism of NEMO linear ubiquitylation by LUBAC (linear ubiquitin chain assembly complex), but is not accessible by biological techniques. Here we perform the chemical ubiquitylation of NEMO using a ligation auxiliary, which only requires a two-step synthesis, and is easily installed onto the lysine side-chain. Chemical ligation occurs directly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Mutations on the surface of NZF1 that binds to NEMO significantly reduce the level of linear ubiquitination of NEMO and, subsequently, NF-κB activation 14 . Moreover, it is suggested that the priming step of NEMO ubiquitination is independent of HOIP catalytic activity 15 , proposing the involvement of HOIL-1L in priming he linear ubiquitination process. HOIL-1L is also shown to regulate LUBAC activities by catalyzing mono-ubiquitination of the LUBAC components, followed by the attachment of linear ubiquitin chains catalyzed by HOIP 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations on the surface of NZF1 that binds to NEMO significantly reduce the level of linear ubiquitination of NEMO and, subsequently, NF-κB activation 14 . Moreover, it is suggested that the priming step of NEMO ubiquitination is independent of HOIP catalytic activity 15 , proposing the involvement of HOIL-1L in priming he linear ubiquitination process. HOIL-1L is also shown to regulate LUBAC activities by catalyzing mono-ubiquitination of the LUBAC components, followed by the attachment of linear ubiquitin chains catalyzed by HOIP 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitinylated proteins and proteins modified by ubiquitin-like modifiers such as SUMO are another class of modified proteins that are actively pursued by protein chemists due to the difficulty in obtaining them recombinantly. Although the role of ubiquitinylation in protein degradation by the proteasome is well established, there is increasing evidence that reversible ubiquitinylation also regulates cell cycle events through nonproteolytic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent report from Haj-Yahya and Lashuel also used a semisynthetic approach for installing a pSer residue in the C-terminal part of the Tau protein and for deciphering the role of this and other PTMs in healthy and diseased states. 19 Ubiquitinylated proteins 20 and proteins modified by ubiquitin-like modifiers such as SUMO 21 are another class of modified proteins that are actively pursued by protein chemists due to the difficulty in obtaining them recombinantly. Although the role of ubiquitinylation in protein degradation by the proteasome is well established, there is increasing evidence that reversible ubiquitinylation also regulates cell cycle events through nonproteolytic mechanisms.…”
Section: Protein Synthesis and The Role Of Ptmsmentioning
confidence: 99%
“…63,64 They have also been adapted to mitigate solubility issues and to aid the assembly of complex, unique targets. 65,66 More recently, there has been a renaissance in flow methods of Fmoc-SPPS and in their automation, both in academia and industry. New instruments and more efficient protocols have been developed that enable cycle times of a remarkable 5 min or less.…”
Section: Mrc Laboratory Of Molecular Biology Cambridge Ukmentioning
confidence: 99%